Radiation and Revolution - Kōso, Iwasaburō, 1955- (Thought in the act., 2020)
In Radiation and Revolution political theorist and anticapitalist activist Sabu Kohso uses the 2011 Fukushima nuclear disaster to illuminate the relationship between nuclear power, capitalism, and the nation-state. Combining an activist's commitment to changing the world with a theorist's determination to grasp the world in its complexity, Kohso outlines how the disaster is not just a pivotal event in postwar Japan; it represents the epitome of the capitalist-state mode of development that continues to devastate the planet's environment. Throughout, he captures the lived experiences of the disaster's victims, shows how the Japanese government's insistence on nuclear power embodies the constitution of its regime under the influence of US global strategy, and considers the future of a radioactive planet driven by nuclearized capitalism. As Kohso demonstrates, nuclear power is not a mere source of energy - it has become the organizing principle of the global order and the most effective way to simultaneously accumulate profit and govern the populace. For those who aspire to a world free from domination by capitalist nation-states, Kohso argues, the abolition of nuclear energy and weaponry is imperative.